2011
DOI: 10.1007/s12088-011-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of Thermostable Xylanase of Bacillus pumilus in Textile Processing

Abstract: Desizing of cotton and micropoly fabrics was done using thermostable xylanase from Bacillus pumilus ASH. Micropoly fabric showed better desizing than cotton under same conditions. Violet scale readings from the TEGEWA test after enzymatic desizing for 90 min at pH 7.0 and at 60°C showed the readings falling in the range of 4-5, indicating good desizing efficiency. During bioscouring the weight loss values and liberation of reducing sugars were highest when EDTA was used along with xylanase. The weight loss val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 18 publications
1
23
0
1
Order By: Relevance
“…Further, it also helped in decreasing in yellowness of fabric by 5.57%. Similarly, xylanase from Bacillus pumilus was studied for enzymatic desizing of cotton and micropoly fabrics (Battan et al 2012). The enzymatic desizing with enzyme load of 5 IU/g at pH 7.0, temperature 60 °C for 90 min resulted in improved whiteness of 0.9% with respect to the chemical process.…”
Section: Xylanase Employed In Textile Industriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it also helped in decreasing in yellowness of fabric by 5.57%. Similarly, xylanase from Bacillus pumilus was studied for enzymatic desizing of cotton and micropoly fabrics (Battan et al 2012). The enzymatic desizing with enzyme load of 5 IU/g at pH 7.0, temperature 60 °C for 90 min resulted in improved whiteness of 0.9% with respect to the chemical process.…”
Section: Xylanase Employed In Textile Industriesmentioning
confidence: 99%
“…The enzymatic desizing with enzyme load of 5 IU/g at pH 7.0, temperature 60 °C for 90 min resulted in improved whiteness of 0.9% with respect to the chemical process. The addition of surfactant such as EDTA improved the desizing and bioscouring efficiency (Losonczi et al 2005;Battan et al 2012;Garg et al 2013).…”
Section: Xylanase Employed In Textile Industriesmentioning
confidence: 99%
“…Increase in reaction time and agitation also results in increase in weight loss percentage of the fabric. 18 It is also observed that the weight loss percentage of cotton is higher initially in the samples treated at 2g/l enzyme concentration. Further it is also found that the wetting time values of fabrics obtained after 90min of treatment were significantly lower to that of fabrics obtained after 60min of treatment whereas further increasing the treatment time from 60 to 120min did not result in much lowering of the wetting time.…”
Section: Effect On Varying the Enzyme Concentration Time And Temperamentioning
confidence: 87%
“…They are additives in the formulation of detergents and, thus, improve the removal of stains of vegetable origin (Kamal et al, 2004). In the textile, enzymes act on cotton cleaning (cotton biopolishing), in order to improve the physical characteristics of the tissue, to assist in the removal of non-cellulosic materials and facilitate alkaline extraction step to improve the access of compounds chemicals to the fiber, leading to a reduction in consumption of these agents and possible environmental damage (Battan et al, 2012;Csiszár et al, 2006).…”
Section: Application Of Thermostable Xylanases In Industrial Processesmentioning
confidence: 99%